2018
DOI: 10.1161/jaha.117.008367
|View full text |Cite
|
Sign up to set email alerts
|

Postsystolic Shortening by Speckle Tracking Echocardiography Is an Independent Predictor of Cardiovascular Events and Mortality in the General Population

Abstract: BackgroundPostsystolic shortening (PSS) has been proposed as a novel marker of contractile dysfunction in the myocardium. Our objective was to assess the prognostic potential of PSS on cardiovascular events and death in the general population.Methods and ResultsThe study design consisted of a prospective cohort study of 1296 low‐risk participants from the general population, who were examined by speckle tracking echocardiography. The primary end point was the composite of heart failure, myocardial infarction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 32 publications
2
33
0
2
Order By: Relevance
“…Previous studies have shown that the assessment of PSS is helpful for the determination of acute ischemic episodes and is more accurate than traditional parameters, such as peak systolic strain and wall thickening. The severity of myocardial PSS can be graded using the PSI . There is an association between myocardial fibrosis and the PSI that may be due to delayed myocardial relaxation, increased left ventricular stiffness, and impaired coronary flow reserve …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that the assessment of PSS is helpful for the determination of acute ischemic episodes and is more accurate than traditional parameters, such as peak systolic strain and wall thickening. The severity of myocardial PSS can be graded using the PSI . There is an association between myocardial fibrosis and the PSI that may be due to delayed myocardial relaxation, increased left ventricular stiffness, and impaired coronary flow reserve …”
Section: Discussionmentioning
confidence: 99%
“…The severity of myocardial PSS can be graded using the PSI. 5 There is an association between myocardial fibrosis and the PSI that may be due to delayed myocardial relaxation, increased left ventricular stiffness, and impaired coronary flow reserve. 23 Postsystolic motion (PSM), which is a common finding in patients with heart failure, especially in patients with a wide QRS and long isovolumic relaxation time, is a robust marker of LV intraventricular dyssynchrony.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations